Antarmuka Mikrokontroller IoT (ESP32) Dengan USB Host max3421e - Rieke Adriati Wijayanti; Ahmad Wilda Yulianto; Dianthy Marya; Muhammad Syirajuddin S.; Nurul Hidayati (Indonesian Society of Applied Science (ISAS), 2020)
Electronic equipment made using old technology or electronic equipment in the entry-level category has not been supported by networking equipment, so for the data communication process, the microcontroller requires interfacing facilities that are in accordance with the electronic equipment used, such as a USB port. With the microcontroller that supports IoT, it allows electronic equipment to communicate over the network. An IoT microcontroller such as the ESP32 is equipped with a WiFi feature but is not equipped with a USB controller feature, while the USB Host max3421e supports the communication process using SPI, so that those two microcontrollers can be used to form an interface using the SPI bus. This interface can be applied to electronic equipment with old technology and entry level electronic equipment for wireless communication. For the needs of making an interface between the ESP32 and max3421e, a software was developed by analyzing the SPI features of the ESP32 and the USB protocol according to the USB device state diagram. The results obtained are the handshake process between systems developed with USB devices in the Low-Speed ​​and Full-Speed ​​categories such as printers, flashdisk, bluetooth mouse and external hard disk, and the device descriptor data of each device tested can be read properly.